Velocity Conference, San Jose, CA 2018. (O'Reilly Media, 2018)
"Velocity San Jose 2018 gathered a highly diverse group of the world's best web ops practitioners, system engineers, and DevOps pros to explore topics related to building and maintaining complex systems, site reliability engineering, infrastructure as code, chaos engineering, and more. This video compilation gives you unfettered access to every keynote address, tutorial, and technical presentation delivered at the conference, more than 50 hours of material to explore at your own pace."--Resource description page